2022
DOI: 10.3389/fpsyg.2022.830842
|View full text |Cite
|
Sign up to set email alerts
|

Using Unified Theory of Acceptance and Use of Technology to Evaluate the Impact of a Mobile Payment App on the Shopping Intention and Usage Behavior of Middle-Aged Customers

Abstract: This research adopted the unified theory of acceptance and use of technology (UTAUT) to emphasize the use of the PX Pay mobile payment app for PX Mart, the most popular supermarket in Taiwan, and examine the degree of involvement as a moderator. The influence of factors related to PX Mart’s target customer groups on their shopping intentions and usage behaviors were discussed, with subsequent benefits and optimization directions. This study indicated the following results. First, performance expectations, ease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Their intention to adopt technology increases when it can improve their lifestyles by providing convenience and efficiency [ 26 , 30 , 76 , 77 ]. The results also suggest that consumer’ decision-making is influenced by the people around them and social influences [ 20 , 29 , 30 , 33 ]. Additionally, the facilitating conditions significantly impacts the BI of consumers.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Their intention to adopt technology increases when it can improve their lifestyles by providing convenience and efficiency [ 26 , 30 , 76 , 77 ]. The results also suggest that consumer’ decision-making is influenced by the people around them and social influences [ 20 , 29 , 30 , 33 ]. Additionally, the facilitating conditions significantly impacts the BI of consumers.…”
Section: Resultsmentioning
confidence: 96%
“…One UTAUT model and social network analysis study found that the recommendations of friends or influencers on the social network significantly impact consumer’ willingness to pay [ 20 ]. Thus, SI is important in influencing BI and decisions regarding technology acceptance [ 33 ]. A previous study believed that SI affects individual behavior, especially when society is important to the person [ 11 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…All in all, the studies on technology adoption done produce mixed results as some find that it is not significant (Aboobucker, 2021) and some (Wong, 2021;and Khater, 2020) find age has influence on certain variables, i.e., social influence, behavioural intention, speed, and security. Liu et al (2022) however finds that generational cohorts have an impact on technology in mobile payment. Hence this study must examine whether digital banking leads to financial inclusion and the stakeholders must take cognisance that the digital banking should not lead to generational digital divide.…”
Section: Conceptual Development and Hypothesesmentioning
confidence: 94%
“…The validity test was performed to ensure that the questionnaire used in the study was understood by all respondents, and the reliability test was carried out to ensure that the questionnaire used in the study guarantees a fairly consistent response from the respondents. This is done so that the research hypothesis testing can achieve its objectives, so that the data used to test the hypothesis must be tested for validity and reliability [13]. Validity and reliability tests are based on LISREL estimates, namely H. loading factor with a significance level and R2 value which is an indicator of the magnitude of the observed variable contribution to the latent variable [14].…”
Section: Prepare Your Paper Before Stylingmentioning
confidence: 99%